MOGAD and NMOSD: insights on patients’ radiological and laboratory findings from a single UAE center - Alzarooni, Hamdan; Inshasi, Jihad; Alawadhi, Ahmad; Giacomini, Paul (Frontiers in Neurology, 2024)
IntroductionAlthough neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody disease (MOGAD) are rare diseases, they pose a significant burden on both society and the healthcare system. This study aims to discuss the demographics and patient characteristics of these diseases in a single center in the United Arab Emirates (UAE).MethodsThis is a retrospective, descriptive study that included patients with either NMOSD or MOGAD treated at Rashid Hospital, UAE during the period between January 2019 and January 2024. Patients were selected and categorized according to NMOSD criteria, aquaporin-4 antibodies, and MOG antibodies. Patient demographics, clinical characteristics, and medical history were retrieved from their medical records and descriptively analyzed in the light of patients’ serological data.ResultsWe identified 34 patients with non-multiple sclerosis atypical CNS inflammatory/demyelinating syndromes. Twenty-seven patients (79.4%) fulfilled the criteria for NMOSD, while seven (20.6%) tested positive for MOG antibodies, fulfilling the criteria for MOGAD. In the NMOSD cohort, 19% (n = 5) were AQP4-antibody negative. Seventy-four percent of the NMOSD cohort and 43% of the MOGAD cohort were female. For MOGAD patients, disease onset was at a younger age (median onset age of 25 years) compared to the overall study population (mean onset age of 28.94 years). Long segment transverse myelitis was only detected in NMOSD patients (33.3%), and brainstem syndrome with area postrema syndrome was more common in the MOGAD cohort (29% vs. 4%). The rate of positive response to intravenous methylprednisolone as initial therapy was comparable across both cohorts (74% in case of NMOSD and 71% in case of MOGAD).ConclusionThis study provides valuable insights into the status of NMOSD and MOGAD in the UAE, highlighting the need for larger, prospective studies to further characterize these diseases in the local population, as well as the need for improved understanding of the epidemiology and management of these rare but debilitating conditions.